PKM Pembuatan Apotik Tanaman Hidup Dan Kebun Buah Mini Untuk Masyarakat Desa - Destini, Rita; Harahap, Rofiqoh Hasan; Sari, Dwi Novita; Kholidah Nasution, Agustini; Perangin-angin, Delima Sari; Frawida, Aulia (LPPI UMN AL WASHLIYAH, 2022)
Covid 19 has caused setbacks in several sectors, including the economic sector. Covid 19 has had a lot of bad impacts on the economic sector such as many layoffs, many prohibitions in carrying out activities outside so that these things cause a decline in the economic sector. So that with the impact, the KKN-PPM team initiated the implementation of creating a healthy environment which is a dream for all communities. This KKN-PPM activity was carried out for 3 weeks where lecturers collaborated with students to create a live plant pharmacy and mini fruit garden for the people of Bengkel village. This pharmacy of live plants such as ginger, turmeric, lemongrass and cassava trees as well as mango, dragon fruit and guava fruit plants. The placement of this plant on the side of the roadside of the Protocol of Perbaungan District, Bengkel Village The goal is to make the environment comfortable. Even though it is a coronavirus pandemic, it does not hinder community service activities on the campus of the University Muslim Nusnatara Al-Washliyah. This activity ran smoothly and very well, because it was supported by the village head and the people of Perbaungan sub-district of Bengkel village